Consumer reactions to H5N1 avian influenza: the Turkish case - Akben, Elif. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The purpose of this thesis is to analyze consumer reactions to the 2005-2006 H5N1 Avian Influenza (commonly known as “bird flu”) outbreak experienced in Turkey. Specifically, we aim at identifying the factors which have an impact on whether consumers are concerned about the safety of poultry products they eat. We also analyze the factors which affect the decision to reduce poultry consumption both during and after the crisis. The data comes from a unique household survey (sample size: 961) constructed for this study. Our estimates reveal that the negative impact of the pandemic on the poultry sector could have been alleviated by first informing consumers about it. Second, campaigns can target consumers with higher income levels and those living in urban areas to help poultry demand to return to preoutbreak levels. We also derive that the impact of government agencies on consumers is significant, but mostly in the post-pandemic period. Policies designed using these results can assist to decrease the negative impacts of future food scares, especially in emerging and transition economies.
Keywords: Poultry industry -- Turkey.; Avian influenza -- Turkey.